Systemic Emergencies in COVID-19 Patient: A Pictorial Review - Marco Albanesi; Diletta Cozzi; Edoardo Cavigli; Chiara Moroni; Gianluca Frezzetti; Lina Bartolini; Vittorio Miele (Tomography, 2022)
Since the first report of the outbreak in Wuhan, China in December 2019, as of 1 September 2021, the World Health Organization has confirmed more than 239 million cases of the novel coronavirus (SARS-CoV-2) infectious disease named coronavirus disease 2019 (COVID-19), with more than 4.5 million deaths. Although SARS-CoV-2 mainly involves the respiratory tract, it is considered to be a systemic disease. Imaging plays a pivotal role in the diagnosis of all manifestations of COVID-19 disease, as well as its related complications. The figure of the radiologist is fundamental in the management and treatment of the patient. The authors try to provide a systematic approach based on an imaging review of major multi-organ manifestations of this infection.